Development of ultra-lightweight foamed concrete modified with silicon dioxide (SiO2) nanoparticles: Appraisal of transport, mechanical, thermal, and microstructural properties - S. Majeed, Samadar S. Majeed; Mydin, Md Azree Othuman; Bahrami, Alireza; Dulaimi, Anmar; Onuralp Ozkılıç, Yasin; Omar, Roshartini; Jagadesh, P. (elsevier, 2024)
Over the last few decades, researchers have devoted significant consideration to the use of nanoscale elements in concrete. Silicon dioxide nanoparticles (SDNs) have been a popular subject of study among the several types of nanoparticles. This article describes the findings of a laboratory investigation that examined the properties of ultra-lightweight foamed concrete (ULFC) including different proportions of SDNs. Wide range of the properties was evaluated specifically the slump flow, density, consistency, flexural strength, modulus of elasticity, compressive strength, split tensile strength, thermal properties, porosity, water absorption, sorptivity, intrinsic air permeability, and chloride diffusion. Additionally, the scanning electron microscopy (SEM) and pore distributions analyses of different mixes were done. Results confirmed a noticeable increase in the mechanical properties of ULFC, with respective improvements in the 28-day compressive, split tensile, and flexural strengths of up to 70.49%, 76.19%, and 51.51%, respectively, at 1.5% of the SDNs inclusion. However, further increases in the SDNs percentage did not result in remarkable enhancements. As the SDN percentage increased from 1.5% to 2.5%, the ULFC’s sorptivity, porosity, water absorption, intrinsic air permeability, and chloride diffusion showed substantial improvements. When compared to the control sample, ULFC with SDNs demonstrated higher thermal conductivity values. The reason for this occurrence was determined to be the smaller pore size observed in the ULFC specimens containing SDNs. A great adjustment in the distribution of pore diameters was witnessed in the ULFC mixes when the percentages of SDNs were adjusted. The ULFC specimens, which included SDNs at the percentages of 0.5%, 1.0%, and 1.5%, indicated a reduction in the total number of large voids measuring 500 nm or more, compared to the control ULFC specimen. The findings of this study highlight the potential benefits of incorporating SDNs into ULFC, which may improve its overall properties.